2001
DOI: 10.1002/ajh.1146
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the occurrence of and risk factors for hemophilia‐associated intracranial hemorrhage

Abstract: Recent studies suggest that rates of intracranial hemorrhage (ICH) increased concomitant with the HIV epidemic among the hemophilia population, but no studies have directly examined factors associated with ICH. To determine ICH rates and identify factors associated with ICH, we performed a nested case-control study of a cohort composed of all hemophilic males identified by a surveillance system. Data were obtained from medical records of care received during 1993-1997. Patients with ICH listed in hospital reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
3
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 10 publications
8
100
3
8
Order By: Relevance
“…Most common first bleeding sites are shown table 15. Similar pattern of bleeding is also reported by another large hospital based retrospective study in 399 newborn 16,17 .Intracranial hemorrhage (ICH), though rare, is the serious complication often misdiagnosed in neonatal period because of vague presentation especially with negative family history. High index of suspicions are necessary to pick these cases.…”
Section: Clinical Manifestationsupporting
confidence: 54%
See 1 more Smart Citation
“…Most common first bleeding sites are shown table 15. Similar pattern of bleeding is also reported by another large hospital based retrospective study in 399 newborn 16,17 .Intracranial hemorrhage (ICH), though rare, is the serious complication often misdiagnosed in neonatal period because of vague presentation especially with negative family history. High index of suspicions are necessary to pick these cases.…”
Section: Clinical Manifestationsupporting
confidence: 54%
“…Intracranial hemorrhage: Intracranial hemorrhage is the serious complication of hemophilia with a significant cause of disability and long term neurological sequelae as many as 60-75% cases 16,17 . Prevalence of symptomatic ICH in all ages varies from 3-12% with a substantial proportion occurring in children 26 .…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…Several reports have suggested an increased incidence of clinically significant intracranial hemorrhage and worse outcomes for patients with hemophilia and inhibitors. [24][25][26][27][28][29] Our study was not powered to detect the benefit of prophylaxis for low-incidence, high-morbidity bleeding events such as intracranial hemorrhage. However, it is reasonable to assume that patients who have a good response to prophylaxis are also likely to have a reduced risk of life-threatening bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…5,14,23 Data from the six-state Hemophilia Surveillance System Project cohort in the United States demonstrated that age greater than 51 years, severe hemophilia, HIV, and the presence of inhibitor were independent risk factors for intracranial hemorrhage. 24 An effect of inhibitor presence on intracranial hemorrhage-associated mortality, however, was not confirmed by UK hemophilia surveillance data. 25 Intracranial hemorrhage has the highest mortality of any hemophilia-related bleeding, and a death rate of 30% has been reported among hemophilia patients age 50 and older with intracranial hemorrhage.…”
Section: Intracranial Hemorrhagementioning
confidence: 98%